DOES ESG PERFORMANCE INFLUENCE CORPORATE TAX AVOIDANCE? AN EMPIRICAL ANALYSIS - Melvin Angelina; Verani Carolina (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to analyze the relationship between environmental, social, and governance (ESG) and tax avoidance in non-financial companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. This study employed a quantitative approach with secondary data, using a sample of 25 companies obtained through purposive sampling and simple regression tests. The results indicate that an increase in a company's ESG value is associated with a decrease in tax avoidance practices. These findings are expected to help investors make informed decisions and encourage companies to integrate ESG into their business activities to minimize the risk of tax avoidance.